2008
DOI: 10.1103/physrevb.77.220102
|View full text |Cite
|
Sign up to set email alerts
|

First-principles solution to the problem of Mo lattice stability

Abstract: The energy differences between the ground state body-centred structure (bcc) and closed-packed face-centred structure (fcc) structures for transition metals in the middle of the series show unusually large disagreements when they are obtained by the thermochemical approach based on the analysis of experimental data or by first-principles electronic structure calculations. Considering a typical example, the lattice stability of Mo, we present a solution to this long-standing problem. In contrast to conventional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
41
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 26 publications
6
41
0
Order By: Relevance
“…This is in agreement with theoretical and experimental studies, where the fcc Mo-phase has been found to be dynamically unstable at low temperatures. 46,47,48 This means that even though the calculated mixing enthalpies of the Mo-rich bcc and Ag-rich fcc ideal random alloys in Fig. 1 appear symmetric with respect to composition, short-range Ag and Mo isostructural clustering in the bcc structure could lower the driving force for global phase separation in Mo-rich alloys more than in Ag-rich alloys with fcc structure.…”
Section: Film Characterizationmentioning
confidence: 99%
“…This is in agreement with theoretical and experimental studies, where the fcc Mo-phase has been found to be dynamically unstable at low temperatures. 46,47,48 This means that even though the calculated mixing enthalpies of the Mo-rich bcc and Ag-rich fcc ideal random alloys in Fig. 1 appear symmetric with respect to composition, short-range Ag and Mo isostructural clustering in the bcc structure could lower the driving force for global phase separation in Mo-rich alloys more than in Ag-rich alloys with fcc structure.…”
Section: Film Characterizationmentioning
confidence: 99%
“…Thermophysical properties such as the specific heat show unusually large anharmonic contributions, and until recently, electronic-structure calculations were in stark qualitative and quantitative disagreement with experiments, e.g., concerning the relative stability between competing phases. 1,2 Turning to lattice defects in bcc metals, a similarly involved situation exists. For instance, the core structure of screw dislocations, which governs the resistance to plastic deformation, is notoriously difficult to model.…”
Section: Introductionmentioning
confidence: 99%
“…21 It has been demonstrated that the errors for lattice stabilities due to the neglect of temperature effects in simulations can be as large as a factor of 2. 22 One class of properties that has attracted particular interest is the elastic behavior of transition-metal nitrides. [16][17][18][19][20] Indeed, it influences many important phenomena that determine the hard-coating performance.…”
Section: Introductionmentioning
confidence: 99%